Daya Saing Kawin Nyamuk Jantan Steril (Culex quinquefasciatus) Skala Laboratorium: Studi Awal Penggunaan Teknik Serangga Mandul dalam Pengendalian Vektor Filariasis Limfatik di Kota Pekalongan - Tri Ramadhani; Upik Kusuma Hadi; Susi Soviana; Zubaidah Irawati; Sunaryo Sunaryo (BALABA: JURNAL LITBANG PENGENDALIAN PENYAKIT BERSUMBER BINATANG BANJARNEGARA, 2017)
Culex quinquefasciatus is the main vector of limfatic filariasis in Pekalongan City. Sterile Insect Tehnique could be an alternative vector control efforts to eliminate filariasis. The success of this technique is depend on the ability of laboratory-reared sterile males with the wild-type females. Indicator of SIT Aplication is determined by the value of the mating competitiveness and sterility to Culex quinquefasciatus (Diptera:Culicidae). The design of the research is an experimental. Gamma irradiation on the pupae (age . 15 hours) with the doses of 0 Gy, 60 Gy, 65 Gy,70 Gy, 75 Gy and 80 Gy in BATAN Jakarta. Male mosquitoes which emerged from the pupa then matting with a normal female. This research observed the mean of females laying eggs ,fecundity, fertility and mating competitiveness. This experimental research was conducted in the laboratory and the data were analyzed by ANOVA.The result showed that irradiation at the trial doses had an effect on fertility of Culex quinquefasciatus, but not had significant effect on fecundity and mating competitiveness . A dose of 70 Gy is the optimum dose with a fertility rate of 1.8% (sterility 98.2%) and C indexs 0,568 can be recommended for futher semi field assays. The number of sterile males were six times compared with the wild population to increase the chances of mating with wild-type females.